Troleybüs Enerji Hatları İçin Matlab Modeli - Dikmen, İsmail Can; Arı, Ali; Karadag, Teoman (Fırat University, 2026)
Bu çalışmada, Türkiye’nin Malatya kentinde hizmet veren troleybüs sisteminin elektriksel ve dinamik davranışları MATLAB/Simulink ortamında modellenmiş ve analiz edilmiştir. Modelde çekiş motorları, eviriciler, troley hattı, doğrultucu merkezleri ve gerilim düşümlerini temsil eden bileşenler ayrıntılı biçimde ele alınmıştır. Gerçek 36 km’lik hat verileri kullanılarak yapılan simülasyonlarda, hat boyunca oluşan gerilim ve akım değişimleri gözlemlenmiş, sistemin 750 V DC besleme altında nominal koşullarda çalıştığı doğrulanmıştır. Elde edilen sonuçlar, modelin gerçeğe yakın davranış sergilediğini ve troleybüs sistemlerinin enerji verimliliği analizlerinde güvenle kullanılabileceğini göstermektedir. Bu kapsamda çalışma, kentsel elektrikli ulaşım sistemlerinin tasarım, planlama ve optimizasyon süreçlerinde referans oluşturabilecek niteliktedir.

This study presents a MATLAB-based simulation model for analyzing the electrical and operational characteristics of trolleybus systems, with a particular focus on the Malatya Trambus line in Turkey. The model was developed entirely in the MATLAB/Simulink environment using a detailed representation of traction motors, inverters, traction rectifier modules (TRMs), and the overhead catenary system. The real 36 km Malatya trolleybus line, supplied by nine transformer groups, was modeled as a segmented DC network to investigate the voltage and current dynamics during operation. A variable-step ODE45 Dormand–Prince solver and discrete Tustin/Backward Euler methods were employed for high-fidelity simulation. The results showed that simulated current and voltage waveforms closely matched real operational data, confirming the model’s accuracy. The trolleybus reached its nominal speed of 65 km/h, with maximum current limited to 600 A and minimum operating voltage never dropping below 220 V. The proposed model provides a reliable platform for analyzing electrical load distribution, optimizing power flow, and improving future energy-efficient public transportation systems in urban environments.
Matlab Model for Trolleybus Power Lines
Keywords: Electrical Energy Transmission; Networks and Systems; Elektrik Enerjisi Taşıma; Şebeke ve Sistemleri; Power Plants; Elektrik Tesisleri; Energy; Enerji